A Comprehensive Review on Liquid Chromatography-Mass Spectrometry (LC-MS): A Hyphenated Technique - Patidar, Anita; Kamble, Priyadarshini (Asian Journal of Pharmaceutical Research and Development, 2025)
The hyphenation of liquid chromatography with mass spectrometry allows for the simultaneous analysis of compounds based on their retention times and mass-to-charge ratios, providing valuable information about the identity and quantity of analytes in a sample. One of the key advantages of LC-MS is its versatility, as it can be applied to a wide range of samples including biological fluids, environmental samples, pharmaceuticals, and food products. This makes it an essential technique in fields such as pharmaceutical analysis, environmental monitoring, metabolomics, proteomics, and forensic science. These techniques have become essential tools for researchers and scientists in various industries, including pharmaceuticals, environmental monitoring, and food safety. One of the most common hyphenated techniques is gas chromatography-mass spectrometry (GC-MS), which allows for the separation and identification of complex mixtures of compounds with high sensitivity and specificity. Another popular technique is liquid chromatography-mass spectrometry (LC-MS), which is widely used in drug discovery and metabolomics studies. These hyphenated techniques offer numerous advantages, such as increased sensitivity, improved selectivity, and faster analysis times. They have greatly enhanced our ability to detect trace levels of contaminants, identify unknown compounds, and quantify analytes accurately. In conclusion, the acknowledgment to LC-MS is crucial for advancing scientific research and improving our understanding of complex chemical systems. Its versatility and sensitivity make it an indispensable tool for modern analytical chemistry. Overall, introductions to LC-MS provide students with a solid foundation in this powerful analytical technique, allowing them to confidently apply it to their own research projects and experiments.